ETHICS AND ARTIFICIAL INTELLIGENCE (AI) IN THE AGE OF AUTOMATION: REEXAMINING MORAL FRAMEWORKS IN TECHNO-ETHICAL DILEMMAS - Panchal, Jetal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper investigates the intricate relationship between ethics and artificial intelligence (AI) in the era of automation, with a primary focus on reevaluating existing moral frameworks in addressing techno-ethical dilemmas. As AI and automation technologies advance rapidly, they raise profound ethical concerns, from algorithmic bias and privacy breaches to the ethical implications of job displacement.The research question at the core of this study is: How do existing moral frameworks in technology ethics, such as utilitarianism, deontology, virtue ethics, rights-based ethics, care ethics, and feminist ethics, address the ethical challenges posed by AI and automation? To answer this question, a comprehensive literature review is conducted, analyzing the historical development of AI and automation, ethical concerns in these fields, and prominent case studies. Methodologically, a qualitative approach is employed, drawing on case studies and examples to illustrate the real-world applications of different moral frameworks in techno-ethical dilemmas.The key findings of this research paper demonstrate that existing moral frameworks provide valuable insights into the ethical dimensions of AI and automation, but they also exhibit limitations when addressing complex, multifaceted challenges. The study reveals that no single framework can comprehensively address all ethical concerns in this domain. Instead, a more pluralistic and context-aware approach to AI ethics is recommended, acknowledging the importance of diverse perspectives and cultural contexts. The implications of this research are profound, as they call for a reevaluation of current practices in AI development, policy-making, and ethical guidelines. By recognizing the limitations of traditional moral frameworks and embracing a more inclusive and adaptable approach, we can navigate the ethical complexities of AI and automation more effectively, fostering a future where technology aligns more harmoniously with human values and societal well-being.